Aloe vera and chitosan-based coatings: a strategy to enhance quality and shelf life of fresh jujube (Ziziphus mauritiana) - Iahtisham-Ul-Haq; Saba Zulfiqar; Hadiya; Sara Shahbaz; Tawfiq Alsulami; Aanchal Sharma; Yash D. Jagdale; Robert Mugabi; Gulzar Ahmad Nayik (International Journal of Food Properties)
Horticultural crops are vital nutrient sources for people in developing countries. However, the quality of jujube degrades quickly due to its delicate nature, leading to a short shelf life. The quality of jujube degrades quickly because of its delicate nature leading to its short shelf life. This study examined the effects of Chitosan (1% & 2%) and Aloe vera (1% & 2%) based edible coatings on extending the post-harvest shelf life of jujube under both room (C1, C2, A1, & A2) and refrigerated storage conditions (CR1, CR2, AR1 & AR2). Jujubes coated with 2% chitosan (CR2) exhibited the lowest weight loss (16.33 ± 1.52 g) after 28 days at 4°C, compared to control samples (15.10 ± 1.65 g). The antioxidant activity (DPPH) decreased significantly under room temperature, from 75.53 ± 1.19% to 17.63 ± 3.96%, while refrigerated samples retained 48.00 ± 3.00%. Ascorbic acid declined by 58% at 25°C and 43% at 4°C. Coated samples also showed higher total phenolic content (124.14 ± 28.25 mg GAE/100 g) compared to uncoated samples (119.41 ± 27.67 mg GAE/100 g). The study concludes that aloe vera (2%) and chitosan (1%) coatings significantly maintain the physicochemical quality and shelf life of jujube under refrigerated storage.